Taxonomy and systematics of species of the tribe Akodontini (Rodentia: Cricetidae) from Western Brazil - Oliveira, Marcus Vinicius Brandão de (2023)
The tribe Akodontini comprise 16 genera and 91 species. Although widely distributed in South America, the tribe is absent in most of Chile and southern Patagonia, and few species occur in the Amazon. The phylogenetic relationships of this tribe, as well as the delimitation of new genera and species, have been revealed through systematic reviews and molecular studies. However, for several taxa, much of the geographic representation was not yet investigated. This is the case of Akodon and Thalpomys, phylogenetically close genera with distinct diversification patterns: 42 and two species, respectively. In Brazil, they occur mainly in the eastern and central regions, occupying areas of the Atlantic Forest and Cerrado. Records and the taxonomic status of members of these genera in western Brazil, in transition areas between the Amazon, Cerrado, and Pantanal, were rarely addressed in systematic studies. The present project aimed to: i) delimit and characterize the taxa within Akodon and Thalpomys, with special emphasis on specimens from western Brazil, ii) estimate the phylogenetic relationships among the species of each genus, and consequently illuminate part of the evolutionary history of the tribe Akodontini. The diversity of both genera was investigated under an integrative approach with karyological, morphological, morphometric, and molecular analyses. The study of these populations of Akodon allowed to recognize two new species, which we named as A. diauarum, endemic to Amazon/Cerrado transitional forests of Mato Grosso and Pará, and A. kadiweu, endemic to dry forests of Mato Grosso do Sul. Moreover, A. dayi was recorded in the dry forests of Mato Grosso, for the first time. These discoveries, along with the results of a densely sampled phylogenetic tree, allowed the recognition of three species-groups within western Brazil: boliviensis group (A. kadiweu), cursor group (A. diauarum, A. montensis), and dolores group (A. dayi, A. toba), all members of a large clade of Akodon that typically occur in lowlands (except for part of the boliviensis group) as recovered by the present phylogenetic hypothesis. The systematic review of Thalpomys allowed a better comprehension of this poorly known genus with: i)_a new hypothesis of a sister-relationship with Necromys, instead of Podoxymys, as proposed by previous studies, ii)_the recovery of a putative new species from Mato Grosso/Rondônia, iii)_redescription of T. cerradensis and T. lasiotis, including new diagnostic characters, with a significant change of their geographic range, iv)_geographic variation across qualitative and quantitative characters, v)_the hypothesis that the diversification of Thalpomys is intrinsically linked to the Cerrado. The integrative approaches of the systematics of Akodon and Thalpomys herein revealed that western Brazil harbors a previously underestimated diversity of Akodontini rodents. This is relevant not only as related to species richness of this area, but also by reveling a faunal component of species endemic to western Brazil. The present study provided further data to the comprehension of the diversification and biogeography of the tribe Akodontini, and calls for attention to the conservation of western Brazil and its Cerrado and transitional dry forest areas, still poorly studied and very diverse.